2020
DOI: 10.1177/1120672120963449
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of two different types of intracorneal implants in keratoconus: A corneal tomographic study

Abstract: Objective: To evaluate changes in visual acuity and corneal tomographic outcomes at 6 months after femtosecond-laser assisted implantation of two different types of intracorneal implants in keratoconus. Methods: A total of 39 keratoconus eyes implanted with two segments KeraRing ( n = 22 eyes) or MyoRing ( n = 17 eyes) were enrolled. Tomographic data (Pentacam system, Oculus) were analyzed and correlated with enhancement in uncorrected (UDVA) and corrected distance visual acuity (CDVA). The tomographic indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…While there was good agreement between the clinical results and the numerical analysis results for Kera355 with both implementation methods, the pocket method induced a higher flattening effect compared with the tunnel incision method. A recent clinical study [35] also confirmed that the pocket method could generally achieve greater regulation of corneal shape, though several factors could still influence this fact, such as the degree of disease, the initial structure of the cornea, and the generated interactions between ICRS and the cornea. From mechanical perspective, in the severe form of keratoconus in which patients suffer severely from tissue degeneration, the pocket incision eliminates intrastromal tissue constancy and strength.…”
Section: Effect Of Icrs On Corneal Deformations and Shape Regularization (Fem Validation)mentioning
confidence: 94%
“…While there was good agreement between the clinical results and the numerical analysis results for Kera355 with both implementation methods, the pocket method induced a higher flattening effect compared with the tunnel incision method. A recent clinical study [35] also confirmed that the pocket method could generally achieve greater regulation of corneal shape, though several factors could still influence this fact, such as the degree of disease, the initial structure of the cornea, and the generated interactions between ICRS and the cornea. From mechanical perspective, in the severe form of keratoconus in which patients suffer severely from tissue degeneration, the pocket incision eliminates intrastromal tissue constancy and strength.…”
Section: Effect Of Icrs On Corneal Deformations and Shape Regularization (Fem Validation)mentioning
confidence: 94%
“…Furthermore, postoperative changes in vision do not regularly correlate with geometric improvements in the cornea [14]. Numerous studies have attempted to determine the relationship between various factors and surgical outcomes to avoid unsatisfactory results [4,7,11,13,[15][16][17][18][19][20][21][22][23][24][25][26]. However, the impact of these factors on ICRS-induced visual outcomes remains inconclusive, and some factors reportedly increase the risk of post-implantation complications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, postoperative changes in vision do not regularly correlate with geometric improvements in the cornea [14]. Numerous studies have attempted to determine the relationship between various factors and surgical outcomes to avoid unsatisfactory results [4,7,11,13,[15][16][17][18][19][20][21][22][23][24][25][26]. However, the impact of these factors on ICRS-induced visual outcomes remains inconclusive, and some factors reportedly increase the risk of postimplantation complications.…”
Section: Introductionmentioning
confidence: 99%